Acute gastrointestinal bleeding. Issue 12 (December 2021) - Evans, Victoria; King, Helen
Acute gastrointestinal bleeding is a common medical and/or surgical emergency that can be caused by a range of diverse pathologies. Gastrointestinal Bleeding can be divided into upper and lower in nature, presenting in sometimes subtly different fashions, but with differing requirements for investigation and management. Prompt identification, risk stratification and treatment are required in order to minimise the ongoing significant morbidity and mortality rates associated with severe presentations of gastrointestinal bleeding.